Estimation of an Overall Value Function in a Sustainable Network of Suppliers: Case Study in a Small Mining Sector - Sepulveda-Salas, J (Springer Nature, 2023)
This study presents a strategic analysis tool to determine the overall value of a supply network incorporating a sustainability index that supports decision-making in the development of industrial public policies. The hypothesis is that the application of a methodological framework based on the circular economy paradigm will leads to a greater overall value in a supply chain than in a network companies where only supplies are coordinated. It is proposed a predictive model to estimate the overall value of the sustainable chain by considering transportation cost and the cost of emissions, production costs, the incidence of the GDP of the industrial sector and a sustainability index which measures expenditures in promotion of circular economy actions. The model is applied to a case study of a supply network in the small, medium and artisanal mining small mining sector in Chile, having an adjusted R-square of 99.6% with an error of 2.48%. With such a model, the supply chain’s overall value can be predicted based on variations of the explanatory variables, thus providing insights about the possible impacts of policies in promotions of the industrial sector. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.